Avaliação de Burnout em policiais militares : a relação entre o trabalho e o sofrimento - Sartori, Leonardo Fávero (2006)
The work is the human activity that builds the organizations and the people. The organization of a work and its conditions can bring problems to the organizations and the workers. In the middle of the current problems of the work there is the burnout syndrome, common in care activities with other people (caregivers). The Military Policemen, risk group for this syndrome, has its very visible work in a reality where the public safety is discussed and reflected daily. The objective of this dissertation is to identify the existent relationship between the conditions and the organization of the military policeman's work and the factors of the burnout syndrome, in a Battalion of Military Police. For so much, a literature revision was accomplished about the Organization of the Work, along the Theories of the Administration and a revision about Mental Health and Work that presents the main studies focuses. A revision is presented about the syndrome of Burnout, its factors (Emotional Exhaustion, Despersonalization and Personal Accomplishment), its causes, consequences and research lines. A revision was accomplished about the Military Police, its historical one, the policeman's work, presenting some studies about policemen's health and burnout in policemen. Some important themes to the policeman's routine, as crime rate, community police, gender, use of the force, legislation, were spoken. The dissertation possesses quali-quantitative nature, it is an exploratory and descriptive study, accomplished in a certain moment. Its analysis level is the policeman's work, being used of the Epidemiological focus, of the studies in Mental Health and Work, for its accomplishment. The collection and analysis of data were accomplished according to methodology proposal of the Laboratory of Psychology of the Work of the University of Brasília (LPT-UnB), named of Integrated Diagnosis of the Work (DIT), following the stages: (a) direct observation on the work; (b) accomplishment of the analysis of the tasks; (c) search of the burnout's factors, through Maslach Burnout Inventory (MBI), adapted by LPT-UnB; (d) individual qualitative interviews (semi-structured). DIT analyzes the objective aspects and the non objectives aspects of the work. Through the observation of the work and of the analysis of tasks it was made the description of the organization of the work and of the conditions of the work in the Battalion in study, starting from the field annotations. MBI was applied collectively, being answered individually, accompanied of a questionnaire of demographic data and a Term of Free and Illustrious Consent (approved by the Committee of Ethics in Research of UEL (CEP/UEL). MBI was answered by 497 individuals, of a universe of 822 policemen in the Battalion. The application was proposed to 675 policemen, and 178 refused to fill the MBI. The data were tabulated and analyzed being used the statistical software SPSS (Statistical Package for Social Science), which crossed the demographics' variables with the burnout factors, with non parametric test of the qui-square, for independence of the variables. Finally, were made three interviews, recorded and transcribed, to look for the repetition of the burnout's factors and look for which the demographics' variables that linked with those factors. The Battalion is characterized as a mechanic bureaucracy (Mintzberg, 2003), if approaching of a model mechanic (Robbins, 2004). MBI identified a level of High Emotional Exhaustion in 37% of the policemen, associated with a high level of Despersonalization (44% of the policemen) and a low level of Personal Accomplishment (58% of the policemen). Through the statistical crossings, observation of the work and interviews, it was verified that the work Condition in the Battalion, linked mainly to the work tools (vehicles, equipment of safety and action equipment) is directly related to high Emotional Exhaustion and the low personal Accomplishment in the work. The factors related with Despersonalization are age, time of service and gender. It is possible to revert such picture with educational measures (trainings, development and accompaniment) and changing the processes of administration of the organization (action limited by the mechanic structure).